A Unified Power Quality Conditioner for Feeder Reconfiguration and Setting to Minimize the Power Loss and Improve Voltage Profile. (15th February 2022) - Huang, Zhigao; Shahbaazy, Farid; Davarpanah, Afshin
Abstract : Using devices such as unified power quality conditioners (UPQCs) in distribution networks seems essential for higher electricity quality. Moreover, distribution network reconfiguration is a suitable model for improving network characteristics, including loss reduction and voltage increase for distribution networks, and is widely used in this era. Here, the study discusses the rechanging of distribution networks for UPQC via proposing an appropriate model for it. In addition to the optimum structure of distribution networks, the most appropriate branch where UPQC must be located and the most appropriate reactive power size with which series and shunt filters must be injected into the grid are determined. The simulations have been applied on two 69- and 84-standard-bus networks. The results of the simulations indicate much power loss reduction and much voltage increase in the presence of UPQC compensators.